STEM Education using Contexts Outdoor : A New Dimension in Developing Creative Problem-solving Competencies - Puchongprawet, Jakkrit; Pongsophon, Pongprapan; Jantarakantee, Ekgapoom (Journal of Education Studies, Chulalongkorn University, 2025)
The purposes of this research were: 1) to study the effects of outdoor STEM education on creative problem-solving competencies, and 2) to study the best practices in outdoor STEM education to develop creative problem-solving competencies. The sample consisted of 9th-grade students. The research approach used for this study is action research. Data was gathered from various sources, including the teacher’s and students’ reflective journals, student tasks, and a creative problem-solving skills test, which demonstrated an internal consistency reliability of 0.82. Qualitative data was analyzed using inductive analysis, while quantitative data was analyzed using descriptive statistics which are mean and percentage. The study found that the best practices for using outdoor STEM education involved: applying steps from the engineering design process to select questions connected with contexts outside the classroom, connecting the studied concepts to real contexts, creating and selecting ideas through various techniques using natural materials, and solving problems along with testing and improving tasks to significantly enhance students' creative problem-solving skills in all areas.